2004
DOI: 10.1152/japplphysiol.00745.2003
|View full text |Cite
|
Sign up to set email alerts
|

Caffeine ingestion does not impede the resynthesis of proglycogen and macroglycogen after prolonged exercise and carbohydrate supplementation in humans

Abstract: The purpose of this study was to examine the effects of caffeine (Caf) ingestion on pro- (PG) and macroglycogen (MG) resynthesis in 10 healthy men. Subjects completed two trials, consisting of a glycogen-depleting exercise, while ingesting either Caf or placebo capsules. Throughout recovery, biopsies were taken at 0 (exhaustion), 30, 120, and 300 min, and 75 g of carbohydrate were ingested at 0, 60, 120, 180, and 240 min. Whereas Caf ingestion resulted in a higher blood glucose concentration and decreased glyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
42
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 35 publications
4
42
0
1
Order By: Relevance
“…Therefore, it appears that the early and rapid increase in PG reflects new glycogen granule formation, whereas the latter increase in MG may represent a slower replenishment of the outer tiers of existing molecules or the transition of PG to MG. These results are consistent with previous reports showing that PG is the predominant form of glycogen synthesized early in recovery (2,6,15). Using biochemical measurements of PG and MG in human skeletal muscle, we have shown that PG accumulation is the initial event during glycogen resynthesis (0 -4 h) followed by increases in MG (4 -24 h) (2).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Therefore, it appears that the early and rapid increase in PG reflects new glycogen granule formation, whereas the latter increase in MG may represent a slower replenishment of the outer tiers of existing molecules or the transition of PG to MG. These results are consistent with previous reports showing that PG is the predominant form of glycogen synthesized early in recovery (2,6,15). Using biochemical measurements of PG and MG in human skeletal muscle, we have shown that PG accumulation is the initial event during glycogen resynthesis (0 -4 h) followed by increases in MG (4 -24 h) (2).…”
Section: Discussionsupporting
confidence: 92%
“…more readily degraded during exercise and is the form that is predominantly synthesized during the early phases of recovery (2,6,15).…”
mentioning
confidence: 99%
“…Clearly, exercise/contraction exerts a positive and prolonged effect on muscle glucose uptake, and this is likely to be an important consideration when assessing the effects of caffeine on glucoregulatory mechanisms, particularly in well-trained athletes after exercise-induced glycogen depletion. Furthermore, the results of Battram et al (1) strongly suggest that the factors driving muscle glycogen synthesis after exercise (i.e., insulin-independent mechanisms, low levels of glycogen at exhaustion, high insulin and glucose concentrations, training status of subjects) may override some of the potentially negative effects of caffeine observed on glucose metabolism at rest in untrained individuals (11,12). Given the variable results of studies that have examined the effects of caffeine intake on muscle glycogen synthesis (9, 10, 28), we measured rates of muscle glycogen accumulation in highly trained individuals throughout 4 h of recovery from an exhaustive exercise depletion protocol during which subjects ingested caffeine in association with a CHO ingestion regimen that conforms to current sports nutrition guidelines (4).…”
mentioning
confidence: 91%
“…Yeo et al (35) demonstrated that compared with glucose alone, caffeine [5 mg/kg body mass (BM)] coingested with CHO increased muscle glucose oxidation during 2 h of submaximal cycling. Battram et al (1) recently reported that caffeine (6 mg/kg BM) ingested by moderately trained subjects during 90 min of glycogen-depleting exercise does not affect the rate of glycogen accumulation when large amounts of CHO (ϳ400 g) are consumed during 5 h of recovery. Clearly, exercise/contraction exerts a positive and prolonged effect on muscle glucose uptake, and this is likely to be an important consideration when assessing the effects of caffeine on glucoregulatory mechanisms, particularly in well-trained athletes after exercise-induced glycogen depletion.…”
mentioning
confidence: 99%
See 1 more Smart Citation